The Impact of Different Si Surface Terminations in the (001) n-Si/NiOx Heterojunction on the Oxygen Evolution Reaction (OER) by XPS and Electrochemical Methods. Issue 4 (17th January 2018) - Tengeler, Sven; Fingerle, Mathias; Calvet, Wolfram; Steinert, Céline; Kaiser, Bernhard; Mayer, Thomas; Jaegermann, Wolfram
Abstract : The interaction between (001) n-Si and NiOx was investigated with regard to the oxygen evolution reaction (OER), applicable either for water splitting or CO2 reduction. Thin layers of nickel oxide were deposited step by step by reactive sputter deposition and analyzed in-situ after each step using X-ray photoelectron spectroscopy (XPS). This was performed for silicon with different surface preparations: H-termination, thermally grown oxide (2 Å) and a monolayer of native oxide (4 Å). Upon contact formation the initial flatband like situation in the Si substrates changed to a 0.35 to 0.4 eV upward band bending for all three heterojunctions, with an alignment of the valence bands favorable to hole extraction. With near identical heterojunction performance and identical NiOx catalyst layers (η(10 mA/cm 2 ) = 0.44 ± 0.01 V vs. RHE on Ni) an equally identical performance for the OER would be expected. While the native oxide covered sample shows the expected performance in cyclic voltammetry measurements the others fall short of expectations. Using chopped light measurements, this under-performance could be attributed to a higher density of defect states at the silicon surface. Apparently a 4Å SiO2 layer is sufficient protection to prevent the formation of defect states during NiOx deposition, thinner protective layers or none at all result in increased defect states, while thicker layers perform poorly due to their high resistance.